أثر العيوب الزوجية على عقد الزواج - كريمة ثلايجية; سناء بلفاضل (My University, 2025)
Abstract This legitimate bond is done through a formal agreement between a couple expressed in the marriage contract, through which they aim to create a family dominated by love, affection and stability, so this contract entails mutual rights and obligations between them by doing what each of them must, and bears his responsibility towards the other party. This contract includes several conditions and elements stipulated in the legal articles within the first chapter expressed in "marriage" of the Algerian Family Code. One of the most important conditions set by the legislator is the existence of a medical certificate before marriage in order to detect any disease or defect that prevents the establishment of this marriage, hinders their lives and does not achieve the desired goal of their marriage. The issue of the impact of these defects and diseases on the marital relationship is one of the most issues raised in the Algerian courts, because the existence of such issues can be an inevitable cause that must be adjudicated, and this is either through annulment when there is a legitimate reason, "whether it is by the will of the parties or beyond their control" or the existence of a permanent defect or incurable disease, such as the injury of one of the spouses to insanity, or by requesting divorce when there is discord or other reasons that we have addressed In this research, the wife is pushed to resort to the judiciary and separation between them, and compensation according to the damage caused to her. ........................ ملخــــــــــــص تعدُ رابطة الزواج من أسمى الروابط الإنسانية، والتي توصف بالميثاق الغليظ. فتتم هذه الرابطة الشرعية عن طريق اتفاق رسمي بين زوجين يُعبر عنه بعقد الزواج والذي يهدفان من خلاله إلى إنشاء أسرة تسودها المحبة والمودة والاستقرار، فيترتب عن هذا العقد حقوق والالتزامات متبادلة بينهما من خلال قيام كل منهما بما يجب عليه، ويتحمل مسؤوليته تجاه الطرف الآخر. يتضمن هذا العقد عدة شروط وأركان تنص عليها مواد قانونية ضمن الباب الاول المعبر عنه "بالزواج «من قانون الأسرة الجزائري. ومن أهم الشروط التي حددها المشرع هي وجود شهادة طبية قبل الزواج من أجل الكشف عن أي مرض او عيب يمنع قيام هذا الزواج، ويعرقل حياتهما ولا يتحقق الهدف المرجومن زواجهما. فمسألة تأثير هذه العيوب والأمراض على العلاقة الزوجية من أكثر القضايا التي تُطرح في المحاكم الجزائرية، لأن وجود مثل هذه المسائل يمكن أن يكون سببا محتوما لابد من الفصل فيه، ويكون ذلك إمَّا عن طريق الفسخ عند وجود سبب شرعي" سواء كان بإرادة الطرفين او خارج عن إرادتهما "او وجود عيب دائم او مرض مستعص، مثل إصابة أحد الزوجين بالجنون، او عن طريق طلب التطليق عند وجود شقاق او غيره من الأسباب التي تطرقنا لها في بحثنا هذا، تدفع الزوجة إلى اللجوء للقضاء والفصل بينهما، وتعويضها حسب الضرر الواقع لها .فوصول الزوجين لمرحلة الفسخ او المطالبة بالتطليق يكون بعد استنفاد كل الحلول والإصلاحات الممكنة للتوفيق بينهما وعدم جدواها. ................................ Résumé Ce lien légitime se fait par le biais d'un accord formel entre un couple exprimé dans le contrat de mariage, à travers lequel ils visent à créer une famille dominée par l'amour, l'affection et la stabilité, de sorte que ce contrat implique des droits et des obligations mutuels entre eux en faisant ce que chacun d'eux doit, et porte sa responsabilité envers l'autre partie. Ce contrat comporte plusieurs conditions et éléments stipulés dans les articles juridiques du premier chapitre exprimé en « mariage » du Code de la famille algérien. L'une des conditions les plus importantes fixées par le législateur est l'existence d'un certificat médical avant le mariage afin de détecter toute maladie ou défaut qui empêche l'établissement de ce mariage, entrave leur vie et n'atteint pas l'objectif souhaité de leur mariage. La question de l'impact de ces vices et maladies sur la relation conjugale est l'une des questions les plus soulevées devant les juridictions algériennes, car l'existence de telles questions peut être une cause inévitable qui doit être jugée, et ce soit par voie d'annulation lorsqu'il existe un motif légitime, « que ce soit par la volonté des parties ou hors de leur contrôle » soit par l'existence d'un vice permanent ou d'une maladie incurable, comme l'atteinte à la folie de l'un des conjoints, ou en demandant le divorce en cas de discorde ou d'autres raisons que nous avons abordées Dans cette recherche, la femme est poussée à recourir à la justice et à la séparation entre eux, et à l'indemnisation en fonction du préjudice qui lui a été causé. Keywords: marriage, marital defects, diseases, divorce.
Keywords: Keywords: marriage; marital defects; diseases; divorce.; الكلمات المفتاحية: الزواج، العيوب الزوجية، الأمراض، التطليق،; divorce; Mos clée : marriage